The Bengal renaissance : identity and creativity from Rammohun Roy to Rabindranath Tagore - Dasgupta, Subrata (Delhi : Permanent Black ; New Delhi : Distributed by Orient Longman, 2007)
Study on the social and cultural transformation as happened in 18th and 19th century Bengal, India.
Machine derived contents note: Acknowledgements vi -- Prologue 1 -- 1 Cognitive Identity and Creative Mentality-in -- Colonial Bengal 4 -- 2 An 'Orientalist' Cognitive Identity-and Its Subversion 21 -- 3 Inventing a Monotheistic Movement 39 -- 4 Constructing a, Cross-Cultural Mentality 72 -- 5 Writing for the People, Composing for a Nation 103 -- 6 Creating a Scientific Consciousness, Refuting a -- Western Belief 127 -- 7 Perceiving the One in the Many 170 -- 8 Composing the Universal Song: Work-in-Progress 201 -- Epilogue: Architecture of a Cognitive Revolution 235 -- Bibliography 246.
Includes bibliographical references (p. [246]-261) and index.
Keywords: Social evolution; Bengal (India) -- Intellectual life -- 18th century; Bengal (India) -- Intellectual life -- 19th century